THE ANALYSIS OF REVENUE SHARING FROM MUDHARABAH FINANCING (Case Study of BMT AL FATH IKMI CIPUTAT) - Mega Rosdiana; Siti Jamilah; Andry Priharta (Asosiasi Fakultas Ekonomi dan Bisnis Perguruan Tinggi Muhammadiyah, 2018)
The purpose of this study is to determine the effect of revenue sharing from mudharabah financing atBMT AL-Fath Ikmi Ciputat. Mudharabah is a business cooperation agreement between two partieswhere the first party (shahibul maal) provides the whole (100%) capital, while the other party becomesthe manager. The margin is the amount of profit agreed between BMT and the customer on the financingtransaction with the sale and purchase agreement, in which margins remain unchanged over the term ofthe financing. This study is quantitative research, which aims to give description about the subject understudy and check the truth of the research result, by using descriptive verification method. The samplesare taken using data collection techniques and are documented by collecting financial statement data.The data processing methods use classical assumption test and simple linear regression analysis. Thenthe conclusion of the result of calculation of statistic test t partial known tcount t, (2.165 2.0322) withsignificant value from mudharabah financing variable equal to 0.0042 less than 0.05 or 5% and havepositive coefficient direction. It can be concluded that Ho is rejected and Ha accepted, which means thatmudharabah financing variables have significant and positive effect on profit sharing.